(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
Three complexes of Ru (II) with triphenylphosphine and 2, 3 and 4-aminopyridine ligands were synthesized. X-ray diffraction patterns (XRD) in powder show that the compounds exhibit crystalline structure. The catalytic activity of the complexes was evaluated in the hydroformylation of estragole in homogeneous phase using different reaction conditions such as temperature, pressure (H2/CO) and ratio of catalyst:substrate. The hydroformylation products were quantified using gas chromatography coupled to mass, allowing verification of aldehydes by their characteristics fragmentation. We found that the complex with 2-aminopyridine is chemoselective to the isomerization product in most conditions, while the complexes with 3-aminopyridine and 4-aminopyridine are regioselective to the products 3-(4-methoxyphenyl)-2-methylpropanal and 4-(4-methoxyphenyl) butanal, when using a pressure of 60 bar. Also found that the catalysts synthesized with 2 and 4-aminopyridine are most active (conversion >95%) when the reaction is carried out at 24 h, 40 bar, 100 ° C and 1:500 ratio.